The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/dmcn.14604
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cerebral palsy phenotypes objectively

Abstract: This commentary is on the systematic review by Pham et al. on pages 1024–1030 of this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Recent exome sequencing and copy number variant array studies have demonstrated that between 10 and 31% of CP cases have a genetic cause 6 14 , with a heterogeneous underlying genetic landscape. Nevertheless, the cohorts included in genetic studies have been diverse and reporting of clinical characteristics of cohorts has been variable 15 , leading to some scepticism amongst the medical community about the validity of these findings 16 . Prior genomic analyses (exome sequencing, DNA microarray, or gene panel 7 , 11 , 14 ) of more than 300 cases from the Australian CP Biobank cohort suggest that genetic aetiology is not limited to individuals without other risk factors, or with other neurodevelopmental comorbidities like intellectual disability, epilepsy or autism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent exome sequencing and copy number variant array studies have demonstrated that between 10 and 31% of CP cases have a genetic cause 6 14 , with a heterogeneous underlying genetic landscape. Nevertheless, the cohorts included in genetic studies have been diverse and reporting of clinical characteristics of cohorts has been variable 15 , leading to some scepticism amongst the medical community about the validity of these findings 16 . Prior genomic analyses (exome sequencing, DNA microarray, or gene panel 7 , 11 , 14 ) of more than 300 cases from the Australian CP Biobank cohort suggest that genetic aetiology is not limited to individuals without other risk factors, or with other neurodevelopmental comorbidities like intellectual disability, epilepsy or autism.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal reflection does not disappear. Some children with cerebral palsy may also be accompanied by mental retardation, epilepsy, behavior disorder, visual, and hearing impairment, which seriously affects their normal life [ 2 5 ]. Moreover, there is no cure for cerebral palsy so far; only the symptoms can be alleviated, which brings extremely serious burden and pain to individuals, families, and even the society [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, artificial intelligence and machine learning support a range of other technological developments for which we can anticipate ethical discussion relating to cerebral palsy (13). In a not-so-distant future, artificial intelligence may allow reliable objective characterization of clinical presentations (14), possibly fed by wearable sensor technology (15,16). As previously demonstrated in other populations, machine learning can now recognize a range of relevant physical activity behaviors in individuals with cerebral palsy with great accuracy (17).…”
Section: Technological Issuesmentioning
confidence: 94%